Pharmacologic Treatment of Polycystic Ovary Syndrome: Alternate and Future Paths - Duguech, Luciana M. Martel; Legro, Richard S. (Seminars in Reproductive Medicine, 2017)
Polycystic ovary syndrome (PCOS) is a complex disorder which interacts with other genetic and environmental factors to cause dysregulation of steroidogenesis and anovulation as well as insulin resistance. Treatments which address the long-term effects of this unique combination of reproductive and metabolic dysfunction are needed. Over the past decade, new insights into the genetic factors of PCOS and biotechnological advances have led to potential treatments for women with PCOS. These treatments include both new potent pharmaceutical compounds and repurposed drugs which target different steps in metabolic-reproductive pathways to improve long-term health of women with PCOS. These new therapies target key enzymes involved in steroidogenesis, regulatory pathways of gonadotropin secretion, or lower oxidative stress. We review in this article the current common treatments of PCOS, recent developments in the field, and current information on the mode of action, efficacy, and safety of emerging therapeutic compounds.
Keywords: polycystic ovary syndrome; genetics; new treatments